Production of Recombinant Horseradish Peroxidase in an Engineered Cell-free Protein Synthesis System - Park, Yu-Jin; Kim, Dong-Myung (Frontiers in Bioengineering and Biotechnology, 2021)
One of the main advantages of a cell-free synthesis system is that the synthetic machinery of cells can be modularized and re-assembled for desired purposes. In this study, we attempted to combine the translational activity of Escherichia coli extract with a heme synthesis pathway for the functional production of horseradish peroxidase (HRP). We first optimized the reaction conditions and the sequence of template DNA to enhance protein expression and folding. The reaction mixture was then supplemented with 5-aminolevulinic acid synthase to facilitate co-synthesis of the heme prosthetic group from glucose. Combining the different synthetic modules required for protein synthesis and cofactor generation led to successful production of functional HRP in a cell-free synthesis system.